Language Functions Used by The Main Characters of The Marriage Story Movie - Shely Martha Sanastia; Mytha Candria (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
People use different utterances by considering the social context in which communication takes place. An utterance may have more than one meaning and function depending on social context and other factors. This study aims to describe the spoken language functions of the main characters, Charlie and Nicole, in the Marriage Story movie. This descriptive qualitative research used Roman Jacobson’s language function classification to categorize the selected utterances found in Marriage Story movie into one of the six functions (emotive, conative, referential, metalingual, phatic, and poetic). To interpret the classified data and the contexts or situations, I relate the language functions to social factors and social dimensions based on Holmes’ categorization. The results show that all six language functions appeared in Nicole and Charlie’s utterances. The data analysis depicts that emotive function is predominantly used by the main characters throughout the whole movie. Moreover, those language functions are influenced by social factors and social dimensions.Keywords: language function; social factor; social dimension; Marriage Story.